Estimation of production and monitoring of a varietal composition of the sown winter barley seeds in the Rostov region - G. A. Filenko; А. А. Dontsova; Yu. G. Skvortsova (Зерновое хозяйство России)
The current paper has presented a detailed analysis of the production of winter barley over a long period, taking into account their sown areas, gross yields and productivity in farms of all categories in the Russian Federation and the Rostov region. The purpose of the study was to estimate the production and monitor the varietal composition of sown winter barley seeds in the Rostov region. In the region, the sown area occupied by winter barley annually amounts to more than 41.1 thousand hectares with a mean yield of 3.9 t/ha. An analysis of the sown winter barley varieties in the Rostov region was carried out according to the year they were included in the State List of the Russian Federation. As a result of study, there was found that there were 6–9 barley varieties included in the State List in the period up to 4 years; 4 ones in the period of 5–8 years; 5–6 ones in the period of 9–12 years; 4–6 ones in the period of more than 12 years. There was established that the largest area under winter barley was occupied by the varieties of local breeding of the FSBSI “ARC “Donskoy” (49.5–58.5 %), about 16.0–25.1 % of the area was occupied by the varieties of the Krasnodar breeding of the FSBSI “NGC named after P.P. Lukyanenko”. There was found out that the most popular varieties in the Rostov region over the past three years were the varieties ‘Erema’ (18.4–18.4 %), ‘Timofey’ (12.5–13.3 %), ‘Vivat’ (11.9–12.7 %), ‘Marusya’ (5.7–12.6 %), ‘Foks 1’ (1.9–3.6 %), ‘Karrera’ (8.7–13.2 %), ‘Iosif’ (7.4–10.2 %), ‘Dobrynya 3’ (1.8–2.9 %), ‘Samson’ (0.6–3.4 %), ‘Luran’ (0.8–4.5 %) and ‘Dostoiny’ (2.6–8.5 %). Thus, to improve the production of winter barley grain in the Rostov region, it is necessary to cultivate varieties that are most adapted to local conditions, have high productivity and grain quality, and are included in the State List for the North Caucasus region.